Shoot Regeneration of Sandalwood (Santalum album L.) by Different Media and Benzile Amino Purine (BAP) Concentrations - Ginting, Beri Adimas Aryanto; Resmisari, Ruri Siti (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green Technology, 2017)
Sandalwood ( Santalum album L.) has a variety of benefits. The crops are harvested sandalwood to be used is the roots and the wood as much to contain the essential oil. Many benefits of sandalwood are not matched with the success of the cultivation of sandalwood judged is still low. The condition encouraged to make a breakthrough the provision of the seeds of sandalwood en masse throughout techniques is in vitro. The composition of media and the addition of the regulator is growing affect success in the culture of tissues. The Woody Plant Medium (WPM) and Murashige and Skoog (MS) a basic media that contains the source of food contain the compound organic and inorganic to growth explant. Sterilization of sandalwood explant is done by washing with detergent, rinsed with flowing water, immersed in fungicide, bactericida, NaCl 5% and ethanol 70% solutions. Sandalwood explant then planted in the WPM  and MS media with the addition of regulator is grow Benzile Amino Purine (BAP). Sandalwood explant that grows in the WPM medium with the addition of BAP 2 ppm provides optimum results in parameters day of the emergence of shoots, the length of shoots and the number of leaves. While parameters the number of shoots optimally if it is growing the MS medium with the addition of BAP 2 ppm.